Pengaruh Substitusi Tepung Kalakai (Stenochlaena Palustris) Terhadap Daya Terima, Daya Kembang dan Kadar Zat Besi Bolu Kukus Sebagai Makanan Selingan Untuk Mencegah Anemia Remaja Perempuan - Zhiyadatul Widaty; Norhasanah Norhasanah; Nany Suryani; Nurul Hekmah (Jurnal Kesehatan Indonesia, 2025)
Kalakai flour can be used as a substitution in steamed sponge cake as an alternative snack for teenage girls which is high in iron. This study aims to determine the effect of substitution of kalakai flour on acceptability (color, aroma, taste, and texture), swellability, and iron content of steamed sponge cake as a snack to prevent anemia in adolescent girls. This type of research is experimental with the research design used being a completely randomized design (CRD). There are 4 types of proportions, namely P0 (100% wheat flour, 0% kalakai flour), P1 (90% wheat flour, 10% kalakai), P2 (80% wheat flour, 20% kalakai flour), P3 (70% wheat flour), 30% kalakai flour) with 3 repetitions. The method used to test for iron is spectrometry.The research panelists consisted of 25 moderately trained panelists. The results of the acceptability test showed that the most preferred treatment by the panelists was P0 (color, aroma, taste, and texture). The results of the swellability test showed that the most swelling treatment was P1 which expanded 65% compared to P3 which only expanded 2%. The highest iron content per 100 g of steamed sponge cake is P3 which is 3.17 mg/g compared to P1 which is 1.79 mg/g. The best treatment judge from the best composition, acceptability test, swellability and iron content was P1. Kalakai steamed sponge can meet the iron needs of teenagers from snacks 10-15% when consuming as much as 87.5 grams, namely 2.5 pieces of sponge in treatment one (P1).